PITX2 gain-of-function mutation associated with atrial fibrillation alters mitochondrial activity in human iPSC atrial-like cardiomyocytes - Benzoni, Patrizia; Da Dalt, Lorenzo; Elia, Noemi; Popolizio, Vera; Cospito, Alessandro; Giannetti, Federica; Dell’Era, Patrizia; Olesen, Morten S.; Bucchi, Annalisa; Baruscotti, Mirko; Norata, Giuseppe Danilo; Barbuti, Andrea (Frontiers in Physiology, 2023)
Atrial Fibrillation (AF) is the most common cardiac arrhythmias worldwide; however, the underlying causes of AF initiation are still poorly understood, mainly because currently available models, does not allow to distinguish the initial causes from the maladaptive remodeling that it induces and perpetuates AF. Lately, genetic background has been proven to be important in AF onset. iPSC-derived cardiomyocytes, being patients’ and mutation’ specific may help to solve this diatribe, by showing initial cell-autonomous changes underlying the development of the disease. The transcription factor paired-like homeodomain 2 (PITX2) has been identify as a key regulator of atrial development/differentiation and the PITX2 genomic locus has the highest association with paroxysmal AF. PITX2 influences mitochondrial activity, and alteration in either its expression or function have been widely associated with AF. In this work we investigate the activity of mitochondria in iPSC-derived atrial cardiomyocytes (aCM) obtained from a young patient (24 years old) with paroxysmal AF, carrying a gain-of-function mutation in PITX2 (rs138163892) and from its isogenic control (CTRL) in which the heterozygous point mutation has been reverted to WT. PITX2 aCMs show higher mitochondrial content, an increased mitochondrial activity and superoxide production under basal condition when compared to CTRL aCMs. However, increasing mitochondrial workload by FCCP or by β-adrenergic stimulation allows us to unmask mitochondrial defects in PITX2 aCMs, which are incapable of responding efficiently to the higher energy demand, determining ATP deficiency.